Ativismo religioso online : a pluridade e a transparência da fé da juventude porto-alegrense católica e evangélica na mídia social Instagram - Vieira, Gabriela Ferreira (2022)
Breaking barriers and conquering religion, among many other sectors, digital transformation impacts and continues to generate constant transformations. With examples of its advantages, the internet and networks and social media increasingly inform, have widespread access and influence people. Among these users, are young Catholics and Evangelicals, who integrate technology with religion and spread their beliefs in creative, inspiring, different and transparent ways. The main objective of this dissertation is to analyze how the digital transformation resulted in behavioral effects of high religious activism, from the various displays of faith in the Instagram profiles of the young Catholic and Evangelical Porto Alegre participants who take part in the movements CLJ – Youth Leadership Course, Guelfos Society, Universal Youth Force Gaúcha and Young Encounters of Faith. To achieve this purpose the methodology used has a qualitative nature, outlines being bibliographic and exploratory research, as well as other sources such as photographs, articles from online newspapers and magazines, social networks, IBGE reports, among others. The sampling was non-probabilistic and directed, typical or intentional and the technique and instrument of data collection conducted was the individual interview, with a structured technique in conjunction with digital ethnography. The analysis was carried out with 8 (eight) youngs, half of them Catholics and the other Evangelicals, 2 (two) per group studied (one young female and one young male), aged 19 (nineteen) to 28 (twenty-eight) years old, active Instagram users and consumers of religious content on the internet. As well as being interviewed, they were also analyzed for their faith publications from their chosen Instagram profiles both feeds and stories for 15 (fifteen) calendar days prior to the interview date and also from previous religious publications posted on the same platform that are located in the highlights, feed and other Instagram formats (reels, IGTV). Topics covered include: virtual plurality, cyberculture, contemporary consumer, medias and social networks, exposure via Instagram, Brazilian religiosity, Catholicism, Evangelicalism, faith coverage in the media, the conceptualization of youth, generations Y and Z, Christian youth and Catholic and Evangelical youth movements. The outcome confirms the online religious activism on Instagram present among the youth of both religions and how much there is pluralism in the ways of expressions of faith originating from the frenetic technological phenomenon.